Wet friction materials with quaternary ammonium salts

By forming a coating containing quaternary ammonium salt on the outer surface of the wet friction material of the wet friction clutch, the glazing problem is solved, the friction characteristics and detergency are improved, and the service life of the system is extended.

CN115053078BActive Publication Date: 2025-02-28SCHAEFFLER TECHNOLOGIES AG & CO KG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180013288.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-04-02
Filing Date
2021-03-29
Publication Date
2025-02-28
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

Friction materials in existing wet friction clutches are susceptible to glazing, resulting in reduced friction characteristics and system failure.

Method used

A coating containing quaternary ammonium salt (QAS) is formed on the outer surface of the wet friction material, and the coating is formed by spraying, brushing or rolling the solution containing quaternary ammonium salt to the outer surface of the substrate and drying it.

Benefits of technology

Effectively prevent glazing, improve friction characteristics, improve the detergent and wear resistance of wet friction materials, thereby extending the service life of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A method for making a wet friction material includes combining filler particles and fibers together to form a substrate; coating an outer surface of the substrate with a solution containing a quaternary ammonium salt; and drying the solution containing the quaternary ammonium salt to form a coating containing the quaternary ammonium salt on the outer surface of the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. non-provisional application No. 16 / 838,197, filed on April 2, 2020, the entire disclosure of which is incorporated herein by reference. Technical Field

[0003] The present disclosure relates generally to friction clutches and plates used in torque converters and motor vehicle transmissions, and more particularly to wet friction materials. Background Art

[0004] The friction material in a wet friction clutch generally works in an oil submerged environment and is usually a paper-based material used to form a friction material ring. It is known to form friction materials by a papermaking process using a Fourdrinier papermaking machine. Summary of the invention

[0005] A method for manufacturing a wet friction material is provided, which includes combining filler particles and fibers together to form a substrate; coating the outer surface of the substrate with a solution containing a quaternary ammonium salt; and drying the solution containing the quaternary ammonium salt to form a coating containing the quaternary ammonium salt on the outer surface of the substrate.

[0006] In an exemplary embodiment, the method may also include, after the solution comprising the quaternary ammonium salt is dried, saturating the inside of the substrate with a substrate binder. The solution comprising the quaternary ammonium salt may include a quaternary ammonium salt, a solution binder and water. The solution comprising the quaternary ammonium salt may also include filler particles. The solution comprising the quaternary ammonium salt may include 0.5 to 5.0% by weight of the quaternary ammonium salt, 0.5 to 5.0% by weight of the solution binder, 0 to 30% by weight of the filler particles and 60 to 98% by weight of the water. Coating the outer surface of the substrate with the solution comprising the quaternary ammonium salt may include spraying, brushing or rolling the solution comprising the quaternary ammonium salt onto the outer surface of the substrate. Coating the outer surface of the substrate with a solution containing a quaternary ammonium salt may include spraying the solution containing a quaternary ammonium salt onto the outer surface of the substrate, the solution containing a quaternary ammonium salt containing 0.5 to 2.5% QAS by weight, 0.5 to 2.5% solution binder by weight, 2.5 to 15% filler particles by weight, and 80 to 98% water by weight. Coating the outer surface of the substrate with a solution containing a quaternary ammonium salt may include rolling or brushing the solution containing a quaternary ammonium salt onto the outer surface of the substrate, the solution containing a quaternary ammonium salt may contain 2.0 to 5.0% QAS by weight, 2.0 to 5.0% solution binder by weight, 10 to 30% filler particles by weight, and 60 to 86% water by weight. The coating containing a quaternary ammonium salt may contain 10 to 50% QAS by weight, 10 to 50% solution binder by weight, and 0 to 80% filler particles by weight. The coating comprising a quaternary ammonium salt may comprise 12.5 to 25% by weight of QAS, 12.5 to 25% by weight of a solution binder and 50 to 75% by weight of filler particles. The solution binder may be nanocellulose, guar gum or an acrylic based emulsion.

[0007] A method for manufacturing a component of a friction clutch is also provided, comprising: manufacturing a wet friction material; fixing the wet friction material to a metal component of the friction clutch, coating an outer surface of a substrate with a solution containing a quaternary ammonium salt and drying the solution containing the quaternary ammonium salt before or after fixing the wet friction material to the metal component.

[0008] Also provided is a wet friction material including a substrate including a fiber matrix and filler particles embedded in the fiber matrix; a binder embedded in the interior of the substrate; and a coating layer including a quaternary ammonium salt on an outer surface of the substrate.

[0009] In some exemplary embodiments of the wet friction material, the coating comprising a quaternary ammonium salt may comprise a quaternary ammonium salt and a solution binder. The coating comprising a quaternary ammonium salt may also comprise filler particles. The coating comprising a quaternary ammonium salt may comprise 10 to 50% by weight of QAS, 10 to 50% by weight of a solution binder, and 0 to 80% by weight of filler particles. The coating comprising a quaternary ammonium salt may comprise 12.5 to 25% by weight of QAS, 12.5 to 25% by weight of a solution binder, and 50 to 75% by weight of filler particles. The solution binder may be nanocellulose, guar gum, or an acrylic-based emulsion. The substrate may comprise a single layer. The substrate may comprise a support layer and an outer layer. The support layer may comprise a first fiber material in a certain proportion and a first filler material in a certain proportion. The outer layer may comprise a second fiber material in a certain proportion and a second filler material in a certain proportion. The proportion of the second fiber material may be less than the proportion of the first fiber material. The proportion of the second filler material may be greater than the proportion of the first filler material.

[0010] A clutch assembly is also provided that includes a metal component and a wet friction material on the metal component. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The present disclosure is described below with reference to the following drawings, in which:

[0012] Figure 1a schematically illustrates a substrate of a wet friction material according to an embodiment;

[0013] Figure 1b Schematic diagram of a coating containing QAS Figure 1a The substrate of the wet friction material;

[0014] Figure 2 shows the wet friction material bonded to the top of the metal part via a heated plate;

[0015] Figure 3 Wet friction material bonded to both sides of a clutch plate of a lock-up clutch assembly of a torque converter is shown;

[0016] Figure 4 A dual layer wet friction material according to another embodiment of the present invention is shown. DETAILED DESCRIPTION

[0017] The present disclosure provides a method of forming a wet friction material comprising a coating comprising a quaternary ammonium salt (QAS) on an outer surface of the friction material. Such a coating can prevent glazing, which is a failure mechanism of friction materials in wet friction systems that involves thermal degradation of automatic transmission fluid components at high temperatures and then deposition on the outer surface of the friction material. Glazing is caused by increased temperatures on the clutch surface due to long sliding periods or high energy engagements, and results in poor friction behavior due to reduced porosity of the friction material. Friction materials with lower porosity may be more easily glazed and benefit from a coating comprising a QAS on the outer surface.

[0018] QAS provides friction improvement and detergency. Adding QAS to friction materials provides the desired friction characteristics while keeping the surface clean from degraded additive residues due to its detergency.

[0019] In one embodiment, QAS is a quaternary ammonium salt having an alkyl chain of -16 to 18 carbon atoms. For example, QAS may be Arquad 2HT-75, which is di(hydrogenated tallow alkyl) dimethyl ammonium chloride.

[0020] Figure 1a , 1b A method of forming a wet friction material according to one embodiment of the present disclosure is schematically illustrated.

[0021] The wet friction material 12 includes a substrate 13 formed of fibers, filler materials and a matrix binder. The fibers may be aramid fibers, organic fibers, carbon fibers and / or glass fibers. The organic fibers may include cellulose fibers or cotton fibers. The filler material may be particles of diatomaceous earth. The substrate binder may be a phenolic resin. Optionally, a friction modifier such as graphite may also be included in the substrate 12. The fibers of 12 may have an average diameter of 45 to 55 microns and an average length of 1 to 2 millimeters.

[0022] In a preferred embodiment, the substrate 13 may contain 30 to 45% by weight of fibers, 25 to 35% of filler materials, and 25 to 40% by weight of a base binder. More specifically, the wet friction material 12 may contain 30 to 35% by weight of fibers, 30 to 35% by weight of filler materials, and 30 to 35% by weight of a base binder.

[0023] Figure 1aThe wet friction material 12 is schematically shown before adding a base binder and before applying a solution containing QAS to a base 13. The wet friction material 12 includes a material base formed by embedding a plurality of diatomaceous earth particles 14 in a matrix of fibers 16 between a first outer surface of the base 13, that is, an upper outer surface 13a in the view of the figure, and a second outer surface 13b, that is, a lower outer surface 13a in the view of the figure.

[0024] The fibers 16 and particles 14 are bonded together in a pulping process that includes forming a mixture of the fibers 16 and particles 14 that are immersed together in a liquid solution and then drying the mixture to remove the liquid. After the fibers 16 and particles 14 are bonded together by the liquid solution, the wet friction material 12 includes a matrix formed by the fibers 16 and diatomaceous earth particles 14 that defines a network of voids 18.

[0025] like Figure 1b Schematically, after the fibers 16 and particles 14 are bonded together, a solution containing QAS is applied to the substrate 13 to form a coating 20 containing QAS on the particles 14 and fibers 16 at the outer surface 13a of the substrate 13. The coating 20 containing QAS may be applied to the outer surface 13a by spraying, rolling, or brushing. During the application of the coating 20 containing QAS, the solution containing QAS may also drip into the substrate 13, covering at least some of the particles 14 and fibers 16 formed between the outer surfaces 13a, 13b in the interior of the substrate with the solution containing QAS, and reducing at least some of the size of the voids 18. The coating 20 containing QAS thus covers at least the outer surface 13a, which is defined as a flat surface of the substrate 13 that contacts a flat surface pressed onto the substrate 13. For example, the flat surface may be considered to be a component against which the friction material 12 is pressed for frictional engagement or against which the friction material 12 is pressed for frictional engagement.

[0026] The solution comprising QAS may comprise QAS, a binder and optional filler particles. The binder in the solution is referred to herein as a solution binder to distinguish it from the binder added to the substrate 14 and referred to herein as a substrate binder. The solution binder may be nanocellulose, such as sodium carboxymethylcellulose, guar gum or an acrylic-based emulsion. The filler particles may be diatomaceous earth. The solution comprising QAS may comprise 0.5 to 5.0% QAS by weight, 0.5 to 5.0% solution binder by weight, 0 to 30% filler particles by weight and 60 to 98% water by weight. The amount of water used in the solution may depend on the method of application. For example, roller coating or brush coating may require about 1 / 6 to 1 / 4 of the amount of water when spraying. For roller coating or brush coating, the solution comprising QAS may comprise 2.0 to 5.0% QAS by weight, 2.0 to 5.0% solution binder by weight, 10 to 30% filler particles by weight and 60 to 86% water by weight. For spraying, the solution containing QAS may contain 0.5 to 2.5% by weight QAS, 0.5 to 2.5% by weight solution binder, 2.5 to 15% by weight filler particles, and 80 to 98% by weight water.

[0027] After applying the solution containing QAS to the substrate 13, water is removed by drying the solution containing QAS to complete the formation of the coating 20 containing QAS, which defines the upper outer surface 12a of the wet friction material 12. Drying can be carried out by hot air blowing drying or drying via a hot plate. In either case, the paper surface reaches a temperature of 90 to 110°C. The QAS coating 20 after drying may contain 10 to 50% by weight of QAS, 10 to 50% by weight of a solution binder, and 0 to 80% by weight of filler particles. In some embodiments, the QAS coating 20 after drying may contain 12.5 to 25% by weight of QAS, 12.5 to 25% by weight of a solution binder, and 50 to 75% by weight of filler particles.

[0028] After the QAS coating 20 is applied to the substrate 13, a substrate binder, for example in the form of a phenolic resin, is added to the wet friction material 12. The substrate binder penetrates through the outer surface 13a into the interior of the wet friction material 12, so that the voids 18 in the interior of the wet friction material 12 are saturated with the water-based phenolic resin 20, but the outer surface 12a defined by the QAS coating 20 is exposed.

[0029] like Figure 2As shown, the wet friction material 12 is then placed on top of the metal component 22, and the wet friction material 12 and the component 22 are bonded together to form a friction assembly. Bonding the wet friction material 12 and the component 22 together includes pressing the wet friction material 12 against the metal component 22 with a heating plate 24 to cure the phenolic resin in the wet friction material 12, thereby fixing the wet friction material 12 and the metal component 22 together. The force of pressing the heating plate 24 against the outer surface 12a of the wet friction material 12 causes the heat of the heating plate 24 to cure the phenolic resin while the lower outer surface 12b of the wet friction material 12 is against the outer surface 22a of the metal component 22. The curing of the phenolic resin stabilizes and hardens the wet friction material 12 to fix the fibers 16 and particles 14 in place, which increases the strength of the wet friction material 12. The adhesive film applied between the surface 12b and the surface 22a forms a permanent connection between the metal component 22 and the wet friction material 12 due to the applied time, temperature and pressure. In a preferred embodiment, the heat at the surface 24a of the plate 24 contacting the outer surface 12a of the outer layer while leaving the QAS coating 20 intact is between 375 and 425 degrees Fahrenheit.

[0030] In another embodiment, instead of applying the solution containing QAS to the substrate 13 before adding the base resin to the substrate 13 and before bonding the wet friction material 12 to the metal part 22, the solution containing QAS is applied to the wet friction material 12 after adding the base resin to the substrate 13 and after bonding the wet friction material 12 to the metal part 22. In one exemplary application, after adding the base resin to the substrate 13 and after bonding the wet friction material 12 to the metal part 22, a solution containing QAS of 2 to 10% by weight and 90 to 98% by weight of water without filler particles and a binder is applied to the wet friction material 12, and then the water is dried. More specifically, a solution containing QAS of 5 to 10% by weight of QAS and 90 to 95% by weight of water may be used.

[0031] Figure 3The wet friction material 12 is shown bonded to both sides of a metal part in the form of a clutch plate 40 of a locking clutch assembly 42 of a torque converter 44. The piston 46 of the locking clutch assembly 42 presses the clutch plate 40 against the inner surface 48a of the front cover 48 of the torque converter 44. The piston 46 contacts the surface 12a of the rear piece of the wet friction material 42 to press the surface 12a on the front piece of the wet friction material 12 against the inner surface 48a of the front cover 48. The piston 46 presses the clutch plate 40 against the front cover 48, thereby locking the locking clutch assembly 42 so that the torque path in the torque converter 44 to the transmission input shaft bypasses the impeller 50 and turbine 52 of the torque converter 44 and instead flows from the front cover 48 to the clutch plate 40 and through the damper assembly 54 to the transmission input shaft, which is connected to the output hub 56 of the torque converter 44.

[0032] Figure 4 A double-layer wet friction material 112 according to another embodiment of the present invention is shown. The double-layer wet friction material 112 includes a substrate 113 formed by a support layer 114 and an outer layer 116. The substrate 113 is formed so that the support layer 114 has a thickness T1 between the upper outer surface 114a and the lower outer surface 114b, the outer layer 116 has a thickness T2 between the upper outer surface 116a and the lower outer surface 116b, and the wet friction material 112 has a total thickness T3 between the outer surface 116a and the outer surface 114b. In a preferred embodiment, the thickness T2 of the outer layer 116 is equal to 10 to 30% of the total thickness T3, and thus the thickness T1 of the support layer 114 is 70 to 90% of the total thickness T3.

[0033] The support layer 114 is a wet friction material formed of fibers, filler materials and a base binder. In a preferred embodiment, the fibers are 60 to 100% by weight synthetic fibers, such as aramid fibers, but may also include cellulose fibers, carbon fibers and / or glass fibers. In another preferred embodiment, the fibers are 75 to 90% by weight synthetic fibers. The cellulose fibers may be in the form of cotton wool or wood pulp. The filler may be diatomaceous earth and / or clay. The base binder may be a phenolic resin, latex or silane. Optionally, a friction modifier such as graphite may also be included in the base layer 10.

[0034] The outer layer 116 comprises fibers, filler materials and a base binder. The fibers may be composed of cellulose fibers. The filler is composed of cylindrical diatomaceous earth, random diatomaceous earth or disc-shaped diatomaceous earth. In a preferred embodiment, the diatomaceous earth particles have an average diameter of 5 to 40 microns. The base binder may be a phenolic resin, latex or silane. Optionally, a friction modifier such as graphite may also be included in the outer layer 116. The composition of the outer layer 116 comprises a higher ratio of filler materials and a lower ratio of fibers than the support layer 114, so that the outer layer 116 is less porous and denser than the support layer 114, has a higher coefficient of friction than the support layer 114 and has a higher wear resistance than the support layer 114. The fibers of the layers 114 and 116 have an average diameter of 25 to 35 microns and an average length of 1 to 2 millimeters.

[0035] In some preferred embodiments, the support layer 114 contains 35 to 60% by weight of fibers, 15 to 40% of filler materials, and 20 to 30% of base binder. More specifically, for higher temperature applications, the base ply may contain 35 to 55% by weight of aramid fibers, 15 to 40% of filler (which in some preferred embodiments consists solely of diatomaceous earth), and 25 to 35% of base binder.

[0036] The outer layer 116 is composed of 35 to 55% diatomaceous earth, 15 to 40% cellulose fibers, and 20 to 30% base binder.

[0037] The wet friction material 112 also includes a QAS-containing layer 120 on the outer surface 116a of the outer layer 116. As similarly described above, a QAS-containing solution may be applied to the outer layer 116 to form a QAS-containing coating 120 on particles and fibers at the outer surface 116a of the outer layer 116 of the substrate 113. As similarly described above, the QAS-containing solution may be applied before the base resin is added to the substrate 113 and before the wet friction material 112 is bonded to the metal part, or the QAS-containing solution may be applied to the wet friction material 112 after the base resin is added to the substrate 113 and after the wet friction material 112 is bonded to the metal part.

[0038] In the foregoing description, the present disclosure has been described with reference to specific exemplary embodiments and examples thereof. However, it will be apparent that various modifications and changes may be made to the present disclosure without departing from the broader spirit and scope of the present disclosure as set forth in the appended claims. Therefore, the description and drawings should be viewed in an illustrative manner rather than in a restrictive sense.

[0039] Reference numerals list

[0040] 12 Wet friction materials

[0041] 12a Upper outer surface

[0042] 12b Lower outer surface

[0043] 13 Base

[0044] 13a Upper outer surface

[0045] 13b Lower outer surface

[0046] 14 granules

[0047] 16. Fiber

[0048] 18 Gap

[0049] 20 Coatings containing QAS

[0050] 22 Metal parts

[0051] 22a Outer surface

[0052] 24 Heating Plate

[0053] 24a Surface

[0054] 40 Clutch plate

[0055] 42 Locking clutch assembly

[0056] 42 Locking clutch assembly

[0057] 44 Torque Converter

[0058] 46 Piston

[0059] 48 front cover

[0060] 48a Inner surface

[0061] 50 Impeller

[0062] 52 Turbine

[0063] 54 Damper assembly

[0064] 56 Output hub

[0065] 112 Double layer wet friction material

[0066] 113 Base

[0067] 114 Support layer

[0068] 114a Upper outer surface

[0069] 114b Lower outer surface

[0070] 116 Outer Layer

[0071] 116a Upper outer surface

[0072] 116b Lower outer surface

[0073] 120 Layer containing QAS

[0074] T1 Support layer thickness

[0075] T2 outer layer thickness

[0076] T3 Total thickness.

Claims

1. A method for manufacturing a wet friction material, comprising: Binding filler particles and fibers together and forming a matrix; coating the outer surface of the substrate with a solution comprising a quaternary ammonium salt; as well as The solution comprising the quaternary ammonium salt is dried to form a coating comprising the quaternary ammonium salt on the outer surface of the substrate. 2 . The method according to claim 1 , further comprising impregnating the interior of the substrate with a substrate binder after drying the solution containing the quaternary ammonium salt.

3. The method of claim 2, wherein the solution comprising a quaternary ammonium salt comprises a quaternary ammonium salt, a solution binder, and water.

4. The method of claim 3, wherein the solution comprising the quaternary ammonium salt further comprises filler particles.

5. The method according to claim 4, wherein the solution containing the quaternary ammonium salt contains 0.5 to 5.0% by weight of the quaternary ammonium salt, 0.5 to 5.0% by weight of the solution binder, 0 to 30% by weight of the filler particles, and 60 to 98% by weight of water.

6. The method of claim 5, wherein coating the outer surface of the substrate with the solution comprising a quaternary ammonium salt comprises spraying, brushing, or rolling the solution comprising a quaternary ammonium salt onto the outer surface of the substrate.

7. The method of claim 6, wherein coating the outer surface of the substrate with the solution comprising a quaternary ammonium salt comprises spraying the solution comprising a quaternary ammonium salt onto the outer surface of the substrate, the solution comprising a quaternary ammonium salt comprising 0.5 to 2.5% by weight of QAS, 0.5 to 2.5% by weight of a solution binder, 2.5 to 15% by weight of filler particles, and 80 to 98% by weight of water.

8. The method of claim 6, wherein coating the outer surface of the substrate with the solution comprising a quaternary ammonium salt comprises rolling or brushing the solution comprising a quaternary ammonium salt onto the outer surface of the substrate, the solution comprising a quaternary ammonium salt comprising 2.0 to 5.0% by weight of QAS, 2.0 to 5.0% by weight of a solution binder, 10 to 30% by weight of filler particles, and 60 to 86% by weight of water.

9. The method of claim 4, wherein the coating comprising a quaternary ammonium salt comprises 10 to 50% by weight of QAS, 10 to 50% by weight of a solution binder, and 0 to 80% by weight of filler particles.

10. The method of claim 9, wherein the coating comprising a quaternary ammonium salt comprises 12.5 to 25% by weight of QAS, 12.5 to 25% by weight of a solution binder, and 50 to 75% by weight of filler particles.

11. The method of claim 3, wherein the solution binder is nanocellulose, guar gum or an acrylic-based emulsion.

12. A method of manufacturing a component of a friction clutch, comprising: The wet friction material is manufactured by the method according to claim 1, The wet friction material is fixed to a metal component of the friction clutch, and the outer surface of the substrate is coated with the solution containing the quaternary ammonium salt before or after the wet friction material is fixed to the metal component and the solution containing the quaternary ammonium salt is dried.

13. A wet friction material comprising: A substrate comprising a fiber matrix and filler particles embedded in the fiber matrix; a binder embedded in the interior of the substrate; and A coating on an outer surface of the substrate comprises a quaternary ammonium salt.

14. The wet friction material of claim 13, wherein the coating layer comprising a quaternary ammonium salt comprises a quaternary ammonium salt and a solution binder.

15. The wet friction material of claim 14, wherein the coating comprising the quaternary ammonium salt further comprises filler particles.

16. The wet friction material according to claim 15, wherein the coating layer comprising a quaternary ammonium salt comprises 10 to 50% by weight of QAS, 10 to 50% by weight of a solution binder, and 0 to 80% by weight of filler particles.

17. The wet friction material of claim 16, wherein the coating comprising the quaternary ammonium salt comprises 12.5 to 25% by weight of QAS, 12.5 to 25% by weight of solution binder, and 50 to 75% by weight of filler particles.

18. The wet friction material of claim 14, wherein the solution binder is nanocellulose, guar gum, or an acrylic-based emulsion.

19. The wet friction material of claim 13, wherein the substrate comprises: Single layer; or A support layer and an outer layer, wherein the support layer comprises a certain proportion of a first fiber material and a certain proportion of a first filler material, and the outer layer comprises a certain proportion of a second fiber material and a certain proportion of a second filler material, wherein the proportion of the second fiber material is smaller than that of the first fiber material, and the proportion of the second filler material is larger than that of the first filler material.

20. A clutch assembly comprising: Metal parts; and According to the wet friction material of claim 13, the wet friction material is fixed on the metal component.

Citation Information

Patent Citations

  • Anticorrosion liquid and anticorrosion member, and preparation method thereof

    CN104419237A

  • Friction material with high performance surface layer

    US20170261057A1